PENGARUH PEMBERIAN RANSUM PABRIK DENGAN PENAMBAHAN TEPUNG DAUN KELOR TERHADAP PERSENTASE KARKAS AYAM KAMPUNG SUPER - Atul Fitri, Widia; Budiman, Cecep; Yani, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Super free-range chickens are a cross between free-range chickens and laying hens. The use of moringa leaf meal is an alternative solution to reduce high ration costs, and moringa leaves are rich in essential nutrients found in their leaves. This study aims to determine the effect of providing factory rations with the addition of moringa leaf meal on the carcass percentage of super free-range chickens. The study was conducted from January 2026 to March 2026 using a completely randomized design with 5 treatments and 4 replications. Data analysis was carried out through analysis of live weight, carcass weight, and carcass percentage using analysis of variance in a completely randomized design (CRD). The results showed that all research variables, such as live weight, carcass weight, and carcass percentage, had the highest average values ​​in the P0 treatment with the 100% Factory Ration + (without moringa leaf flour), with an average live weight ranging from 1,506-1,594 grams per head, a carcass weight of 919-986 grams per head, and an average carcass percentage ranging from 60.40-61.99%.